Ciencia y construcción del pensamiento - Moreno Marimón, Montserrat (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Two didactic approaches are considered in this paper: the direct transmission of knowledge and the constructivist model, with an analysis of the conceptions they imply on intelligence and how it works. The contribution that the evolution of science itself may bring to the process of individual learning is autlined.